Cakupan Kesehatan Universal (UHC) Pekerja Sektor Informal di Indonesia - Dodi Satriawan; Agus Joko Pitoyo; Sri Rum Giyarsih (TATALOKA, 2020)
Health insurance receives a great deal of attention in the SDG’s, where one of its main targets is to guarantee a healthy life and to encourage welfare for all people of all ages or later to be called Universal Health Coverage (UHC). In Indonesia there are more informal workers than formal sector workers, but almost half of informal sector workers work without health insurance protection. This study aims to determine the achievement of UHC in terms of ownership of health insurance for informal sector workers. The database used in this study was sourced from SUSENAS 2018. Data processing and analysis techniques were carried out in a quantitative descriptive form of a single frequency table and a cross table. The results showed that based on socio-economic and demographic characteristics, Indonesian informal sector workers were dominated by men, living in rural areas, being married, being heads of households (KRT) and their partners, aged 18-44 years, having a population registration number (NIK) ), only completed the highest level of basic education, worked in industrial businesses, had no health complaints, was in households with the lowest 40 percent economic status, and did not self-medicate when ill. The study also found that there was still considerable variation in the achievement of UHC between provinces in Indonesia. When viewed by province, Aceh is the province with the highest percentage of health insurance ownership or UHC reaching 94.77 percent. Meanwhile West Kalimantan is the province with the lowest percentage of health insurance ownership, which is only 40.73 percent.